Extra hepatic bile duct injury after laparoscopic cholecystectomy: a retrospective study - Gupta, Ankit; Agrawal, Saurabh; Sharma, Namrata; Parth, Nakum (International Surgery Journal, 2020)
Background: Laparoscopic cholecystectomy (LC), being one of the most common performed surgical procedure among the basic surgeries. Incidence of common bile duct (CBD) injury as high as 1.4-3% has been reported in some studies. The aim of this study was to estimate the incidence and predictors of CBD injury who underwent elective laparoscopic cholecystectomy. Methods: A retrospective observational study conducted at Heritage Institute of Medical Sciences, Varanasi, Uttar Pradesh India. Data was collected for a period of 1 year between March 2019 till 2020. Results: In majority of laparoscopic cholecystectomy we encountered moderate degree of difficulty. Extra hepatic bile duct injuries occurred in 1.4% of cases and were classified according to Strasberg classification. Type A injury was most common followed by type E2. Most major bile duct injuries were recognized intraoperatively. No mortality was noted in our study. Conclusions: Bile duct injuries is a major complication of laparoscopic cholecystectomy with significant morbidity and mortality, reduced survival impaired quality of life and subsequent litigations. Majority of bile duct injuries, results mainly from the surgeon’s inexperience, misinterpretation of anatomy and poor surgical techniques.